E-ARCHIVE APPLICATION BASED ON WEB (CASE STUDY: PT DIRGANTARA INDONESIA (PERSERO)) - Raynawan Herwahyudi; Riki Permana; Dede Rohmat; Muhammad Bayu Hadi; Azizah Zakiah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In this research, the author will build a system to assist employees in archiving documents at PT Dirgantara Indonesia by building a "Website-Based E-Archive Application" system. The approach to the development of this software is to use the prototype method. This prototyping method includes communication, rapid planning, rapid design models, prototype development, and submission and provides feedback. The database used in the development of this software is MySQL and the coding used in the development of this software is a Codeigniter and bootstrap framework. In this research, the authors built software that is expected to be able to assist employees in archiving documents at PT Dirgantara Indonesia.